Dynamics of Dietary Mercury Determined by Mercury Speciation and Isotopic Composition in Dicentrarchus labrax - Pinzone, Marianna; Cransveld, Alice; De Boeck, Gudrun; Shrivastava, Jyotsna; Tessier, Emmanuel; Bérail, Sylvain; Schnitzler, Joseph G.; Amouroux, David; Das, Krishna (Frontiers in Environmental Chemistry, 2022)
Seafood has great ecological and nutritional value for human and wildlife communities. However, accumulation of mercury (Hg) in fish is a concern to animal and human health. There is a crucial need to understand Hg speciation in marine organisms through controlled feeding experiments. This study represents a first assessment of the biological processes that may influence Hg bioaccumulation and dynamics in a marine predatory fish. We conducted a feeding experiment to investigate the dynamics of MeHg and iHg, as well as Hg isotopes in the liver and muscles of captive juvenile seabass (Dicentrarchus labrax). Three groups of juvenile seabass were fed in captivity during 3 weeks of acclimatization and 6 weeks of experiment. Each group was fed with pellets containing environmentally relevant MeHg concentrations (Control, 200 and 500 ng g-1 dw). We monitored the evolution of MeHg and iHg concentrations as well as Hg isotopic values in liver and muscle. We determined Hg dynamics of with respect to the contamination level in the fish diet. Muscle δ202Hg and Δ199Hg turnover rates ranged between 33 and 14 days (Low diet) to 5 and 9 days (Mod diet). Liver δ202Hg and Δ199Hg turnover rates ranged between 3 and 7 days (Low diet) to 3 and 2 days (Mod diet), respectively. Hg species concentrations and δ202Hg varied over time between diet groups and tissues, showing the occurrence of internal mass-dependent fractionation (MDF). No significant intra-tissue and temporal Hg mass-independent fractionation (MIF) was observed. The results of our experiment are strongly in favor of the existence of MeHg demethylation in a coastal predatory fish exposed to low to moderate concentrations of environmental Hg. The decrease over time of δ202Hg in muscle of seabass from the most contaminated diet was accompanied by a temporal increase in iHg, pointing to possible Hg detoxification processes occurring in this tissue when dietary Hg exposure is high. The absence of Hg MDF and different turnover between muscle and liver in seabass exposed to 500 ng Hg g-1 confirmed that Hg speciation and bioaccumulation in juvenile fish are controlled by Hg levels and speciation in their diet.